DESIGN AND CHARACTERIZATION OF A SIMPLE TEMPERATURE SENSOR BASED ON A POLYMER SINE S-BEND OPTICAL WAVEGUIDE STRUCTURE - Yulianti, Ian; Hidayah, Rizki Roqissatul; Leonardy, Joshu; Fianti, Fianti; Sunarno, Sunarno; W. P, Wasi Sakti; Utomo, Galih R.; Prayogo, Defrian; Mufatihah, Nishfa (Universitas Mataram, 2025)
This study presents the design, fabrication, and performance evaluation of a sine S-bend embedded square-core optical waveguide for temperature sensing applications. The waveguide was fabricated using a straightforward and cost-effective CNC milling technique, with PMMA as the cladding and unsaturated polyester resin (UPR) as the core material. Three different bend heights (0.5 cm, 0.6 cm, and 0.7 cm) were investigated to assess their effects on sensor sensitivity, response time, accuracy, and hysteresis. Results showed that increasing the bend height enhanced the sensor sensitivity, with the highest sensitivity of 0.0283 dB/°C achieved at a bend height of 0.7 cm. The response time was consistently maintained at approximately 40 seconds across all samples. The sensor exhibited excellent accuracy, reaching up to 99.31% at a bend height of 0.5 cm. The maximum hysteresis observed was 0.202 % at a bend height of 0.7 cm, indicating stable performance during thermal cycling. These results confirm that the integration of a sine S-bend structure, smooth core surface, and precise waveguide dimensions can significantly improve sensor performance while maintaining a simple and scalable fabrication process.